A Hong Kong validation of working alliance inventory – short form – client. Issue 1 (2nd July 2016) - Hsu, Sharon; Zhou, Ruth De-Hui; Yu, Calvin Kai-Ching
ABSTRACT: As a crucial factor in successful therapy outcome, evaluating and measuring the therapeutic alliance is an essential component to promoting understanding of successful therapeutic experiences. However, few instruments are contextualized to the Chinese culture. This study aims to validate the factorial structure of a Chinese short form of the Working Alliance Inventory (WAI-S) with a sample of 146 Chinese clients at a university counselling centre in Hong Kong. The confirmatory factor analysis found that the original three-factor model was not a fit one in the Hong Kong context. Exploratory factor analysis and reliability tests favour a 9-item or one-dimension structure in the Hong Kong context. The three subscales of bond, task and goal were not found to have significant conceptual distinction.